Comparative Analysis of Global AI Ethics Frameworks and Islamic Ethical Principles in Financial Technology - Onike Morufu Abdul-Azeez (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2025)
AI has inevitably become part of all areas of business and society, including banks and finance houses, and this has necessitated the formulation of various AI ethical frameworks like that of international organisations like UNESCO and EU among others. However, with due consideration of the uniqueness of Islamic finance, guided by Islamic ethical principles, which is built on objectives of shar’ah (maqasid As-Shar’iah), which emphasize benefit’s promotion (that is, jalb al-maslahah) and harm prevention (that is, dar’ al-mafsadah, there is need to explore the possible areas of convergence, divergence or gaps between the global AI ethical principles as prepared by the EU, OECD, UNESCO among others and Islamic finance ethics enshrined in maqasid as-Shariah, therefore, the aim of this paper is to comparatively analyse global AI ethics frameworks as well as Islamic ethical principles, particularly from maqasid as-Shariah perspective, by devising a shariah compliant framework of Islamic AI ethics principles for implementation in the Islamic FinTech sector. The study adopts qualitative content analysis methodology, supported by thematic analysis through manual tagging of the various ethical principles. Findings show that there is a substantial alignment between the three reviewed global AI ethics principles and Islamic ethics principles, not with standing the issues of intention and sources of the ethics—secular and divine. The resultant framework would help in guiding AI development in Islamic fintech.